Analisis Kebebasan Artistik dalam Mendukung Children’s Well-Being pada Anak Usia Dini - Glisna Nayla Saskiani; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This research evaluates the significance of artistic autonomy in promoting the holistic well-being of young learners during early childhood. By granting children the liberty to manifest their ideas, emotions, and imaginative faculties through diverse creative mediums, artistic freedom serves as a fundamental catalyst for their emotional, social, and psychological maturation within educational frameworks. Adopting a qualitative methodology centered on library research, this study synthesizes data from peer-reviewed journals and scholarly texts published over the past five years. The data acquisition process involved systematic literature retrieval utilizing specific descriptors such as